Peran Permainan Fisik Motorik Kasar dalam Mendukung Iklim Pembelajaran yang Aktif dan Menyenangkan di PAUD - Zannah, Raudatul; Malik, Lina Revilla (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to examine the role of gross motor physical play in supporting the creation of an active and enjoyable learning environment at TK Tiara Pertiwi Loa Janan. Gross motor physical play, such as running, jumping, and obstacle courses, is used to develop children's gross motor skills as well as enhance their engagement and motivation in learning. This research employs a descriptive qualitative method with data collection techniques including observation, interviews with teachers, and documentation of learning activities. The results show that gross motor physical play can create a more dynamic, enjoyable learning atmosphere while supporting children's physical, social, emotional, and cognitive development. Additionally, this type of play also plays a role in overcoming children's boredom during learning sessions and enhancing social interaction among students. Despite challenges related to limited facilities, gross motor play can still be adapted creatively by teachers. This study concludes that gross motor physical play has a positive impact on creating an active, enjoyable, and effective learning environment at TK Tiara Pertiwi.